A revelação e a glorificação do λόγος: uma análise exegético-teológica a partir do evangelho de João - Aloísio Rengel, Douglas (Vox Scripturae - Revista Teológica Internacional, 2013)
The research "The Revelation and the Glorification of λόγος: an analysis exegetic- theological starting from the Gospel of John" deepen the understanding of word glory from an exegetic-theological analysis of the Gospel of John. Nowadays it's common to talk about the theme glory, however, the starting point many times is the human glory, letting the glory of God in the background. There also confusion of meanings and misconceptions about this theme, maybe due to the contradiction presented in the cross, in which the glorification occurs both in suffering as in the exaltation. The biggest aid to understanding this theme is the Holy Scriptures, being that the Gospel of John brings rich contributions. So, first of all this research puts its focus on the Old and New Testaments, describing how the term glory is used in the Bible and the possible relation between the Written Priestly and the Gospel of John. The second moment is the principal focus of the research, having as its starting point the Gospel of John. The evangelist presents in a clear way how God's glory is revealed to be human being, namely, by means of Jesus Christ. The glory is revealed, firstly, in the incarnation of the λόγος (logos). So, Jesus Christ is the subject of the revelation of God's glory. This revelation accompanies the life of Jesus, manifesting by means of signs and, mainly, in the relationship of the Son with the Father, that has as single target the cross. The glorification of Jesus is the way of the cross, in which the glory is revealed in the midst of suffering and exaltation. After the departure of Jesus, it's up to παράκλητος (paráklêtos) accomplish the work, having as target the glorification of Christ. And with the aid of the παράκλητος (paráklêtos) that the disciples can accomplish the work in which they were entrusted, can thus glorify God in their lives. However, this is not a task only of the disciples, but extends to every Christian. So the last time of this research is reserved to give the necessary impetus to the Christian can glorify God, in words and actions, besides presenting the final considerations of this research.
Keywords: Glory; Glorification; Glorify; Revelation; John; Cross; Signal